2020
DOI: 10.12688/f1000research.25468.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of chronic cough: similarities and differences between children and adults

Abstract: Cough is a natural process that protects the airway. Cough can occur spontaneously or voluntarily. It is considered chronic when it is present for longer than 4 weeks in children or 8 weeks in adults. In both, chronic cough causes patient distress and increased healthcare utilization. Etiologies of pediatric chronic cough include asthma, protracted bacterial bronchitis, tracheomalacia, habit cough, and various systemic disorders. While some diagnoses are identifiable by careful history alone, others require te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 71 publications
(112 reference statements)
0
15
0
1
Order By: Relevance
“…Insulting/swelling factors (IL-lÎ 2 , etc.) can be written down through NF-KB nuclear-written version of spoken word factor channels, or other pathways cause increased expression [ 7 ]. There is no brought together as one end/end result on the role and legal/law-based machine/method/way of HBD2, and there are few medicine-based studies on its relationship with traditional Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Insulting/swelling factors (IL-lÎ 2 , etc.) can be written down through NF-KB nuclear-written version of spoken word factor channels, or other pathways cause increased expression [ 7 ]. There is no brought together as one end/end result on the role and legal/law-based machine/method/way of HBD2, and there are few medicine-based studies on its relationship with traditional Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of pediatric chronic cough included asthma, postinfectious cough, bronchiectasis, airway malacia, and protracted bacterial bronchitis. In contrast, common causes of chronic cough in adults are gastroesophageal reflux, asthma, and upper airway syndrome (e.g., post-nasal drip) [ 78 ]. In our studies, we found that the pooled prevalence of chronic cough in adults was lower than that of children (adults vs. children: 6.22% [95% CI 5.03–7.41%] vs. 7.67% [95% CI 6.24–9.11%]).…”
Section: Discussionmentioning
confidence: 99%
“…In the convolution stage (Figure 2), the parameters of the pretrained language model were transferred to the disease prediction model through fine-tuning. We set the kernel size as [3,4,5] for the disease prediction model. To avoid information loss, the width of the convolution kernel was set as the same as the dimension of the word vector, and each kernel had 128 output channels.…”
Section: Algorithmmentioning
confidence: 99%
“…In nonspecialized pediatric medical institutions, the proportion of children with cough as the first chief complaint is more than 35% (2). Cough is considered chronic in children when it is present for longer than 4 weeks (3). Etiologies of pediatric chronic cough include asthma, bacterial pharyngitis, influenza (FLU), acute upper respiratory tract infection, suppurative tonsillitis, and bacterial bronchitis.…”
Section: Introductionmentioning
confidence: 99%